EMPING MADE OF CASSAVA IN SUKYAMAI VILLAGE SUB-DISTRICT PULO BANDRING DISTRICT ASSAHAN - Nugrahadi, Eko Wahyu; Siagian, Sahat; Atmojo, Wahyu Tri (Journal of Community Research and Service, 2018)
AbstractGrated chips business developed by Mr. Bakri and Mrs. Armawati in Sukadamai Village Pulo Bandring District is still less developed and needs to be assisted. The process of grated chips production is still constrained by the low skills or innovation of processed products made from cassava produced. The two partners only make the grate, while the competition for this business continues to increase. Each day the chips grated production of these partners business can produce a total of 60 kg / day or 56 packs of grated chips. Beside that, there is still modern markets demand or cake shops that can not be fulfilled due to the lack of knowledge of partners about innovative products based on cassava and packaging design. In relation to the problems faced by both partners, Pak Bakri and Mrs. Armawati, then in the program of dedication to the community in accordance with the agreement of both partners have been planned and realized the existence of training and production simulation by making new products in the form of emping based sweet potato that can be produced by these two partners with total 90 kg / day or 120 packs/day using a cassava grinder. It also planned the procurement of packaging design tools to assist marketing programs in the fulfillment consumer demand of modern market or cake shops. The purpose of all these activities is to maintain the continuity of business or continuity of grated chips business developed by Mr. Bakri and Mrs. Armawati in Sukadamai Village Pulo Bandring sub-district. The success rate of this devotion program to community has been completed, such as: 1. There is a new product that can be produced by the business of Mr. Bakri and Mrs. Armawati, 2. The existence of cassava grinder, 3. The existence of packaging design tools, 4. The existence of packaging design.Keywords: Product Innovation, Emping made of Cassava, Packaging Design